Preliminary Evidence on the Use of Chatbots to Support Junior Software Professionals in Process Guidance - Neves, Fernando Rafael Serra; Andrade, João Victor Machado de; Furtado, Julio Cezar Costa (Anais da Escola Regional de Informática Norte 2 (ERIN 2); 2025: Anais da XVIII Escola Regional de Informática Norte 2DO - 10.5753/erin.2025.15891, 2025)
This study explores whether AI-powered chatbots can enhance task performance and information access for junior professionals. A controlled experiment compared two groups: one used a chatbot, the other a wiki with expert support. Participants completed three tasks of varying difficulty and answered a feedback questionnaire. Preliminary results show that the chatbot group performed better, with statistically significant differences. They also perceived the chatbot as more accessible and efficient, despite noting issues with answer contextualization. These findings suggest chatbots are promising tools for onboarding and learning, though improvements are needed to handle more complex scenarios effectively.